Lithium ion battery electrolyte containing unsaturated carboxylic ester compound

By using unsaturated carboxylic acid ester compounds, cyclic sulfate ester compounds and lithium salt additives with specific structures in the lithium-ion battery electrolyte, a flexible low-impedance SEI film structure is formed, which solves the shortcomings of lithium-ion batteries in high-temperature cycle and low-temperature fast charging performance, and achieves the efficient performance of the battery under different temperature conditions.

CN119627211APending Publication Date: 2025-03-14ZHEJIANG LANTIAN ENVIRONMENTAL PROTECTION HI TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311169285.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrolyte has shortcomings in high-temperature circulation and low-temperature fast charging performance, especially in long-term circulation and high-temperature environments, the battery performance is prone to deterioration.

Method used

An electrolyte containing an unsaturated carboxylic acid ester compound and a cyclic sulfate ester compound is used, and the SEI film structure is modified by a lithium salt additive of a specific structure to form an interface layer with flexibility and low impedance.

Benefits of technology

It significantly improves the high-temperature circulation and storage stability of lithium-ion batteries, while improving the low-temperature discharge performance, ensuring the efficient performance of the battery under different temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004443324680000021
    Figure BDA0004443324680000021
  • Figure BDA0004443324680000031
    Figure BDA0004443324680000031
  • Figure BDA0004443324680000032
    Figure BDA0004443324680000032
Patent Text Reader

Abstract

The invention discloses an unsaturated carboxylic ester compound-containing lithium ion battery electrolyte, which comprises a main lithium salt, a non-aqueous solvent and an additive, and the additive at least comprises an unsaturated carboxylic ester compound as a first additive, a cyclic sulfate compound as a second additive and a lithium salt additive as a third additive, the specific structure is shown in the specification. When the first additive, the second additive and the third additive are added into the electrolyte to be applied to the lithium ion secondary battery, the second additive is added to facilitate the inhibition of the consumption of the first additive in the formation stage, and the second additive and the first additive cooperate to improve the high-temperature storage performance, the high-temperature cycle performance and the normal-temperature cycle performance of the battery; by adding the third additive, the internal resistance of the battery can be further reduced, and the low-temperature discharge performance is improved, so that the high-temperature and low-temperature performance of the battery can be considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium ion battery electrolyte, in particular to a lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound and application thereof. Background Art

[0002] Lithium-ion secondary batteries have a wide range of uses as power sources, especially in recent years, as power sources for electric vehicles or consumer electronics, power storage, etc. With the continuous development of the above products, people have put forward higher requirements on the performance of lithium-ion secondary batteries.

[0003] During the charge and discharge process of lithium-ion batteries, the negative electrode active material easily reacts with the electrolyte, causing the electrolyte to decompose. The additive can form a solid electrolyte interface layer on the negative electrode surface, thereby inhibiting the decomposition reaction of the solvent molecules in the electrolyte and improving the battery stability. However, the electrode interface is easily damaged after a long cycle or high temperature environment, resulting in a decrease in its protective performance, and the battery performance deteriorates accordingly.

[0004] In order to improve the electrochemical performance of the battery, Sony's patent JP2009152133A discloses the use of propargyl acrylate as an additive to improve the storage stability of the battery; Ube Industries' patent CN101981749A discloses the use of di(2-propynyl) itaconate to form a highly thermodynamically stable interface layer at the electrode interface, thereby improving the high-temperature cycle stability of the battery.

[0005] However, although the above-mentioned additives can improve the high temperature performance and storage stability of the battery to a certain extent, their low temperature performance is relatively poor. It is necessary to develop a formula of additives or develop new additives to obtain a lithium-ion battery electrolyte with both high and low temperature performance. Summary of the invention

[0006] In order to solve the problems existing in the background technology, the present invention proposes a lithium-ion battery electrolyte containing an unsaturated carboxylic acid ester compound, which can simultaneously improve the high-temperature cycle performance and low-temperature fast charging performance of the battery. The electrolyte can further improve the low-temperature performance of the battery while improving the normal temperature cycle, high-temperature cycle and high-temperature storage stability.

[0007] The present invention has found through research that: although unsaturated carboxylic acid ester compounds can form a relatively strong negative electrode SEI film structure, when used alone, they are rapidly consumed in the formation stage, which not only makes it impossible to continuously repair the electrode-electrolyte interface in long-term cycles, but also the consumption in the formation stage causes the battery resistance to increase and the ion transmission speed in the battery to drop sharply, ultimately resulting in a decrease in the low-temperature performance of the battery.

[0008] Further research found that: unsaturated carboxylic acid ester compounds with specific structures have synergistic effects with cyclic sulfate compounds. Cyclic sulfate compounds can significantly inhibit the consumption of unsaturated carboxylic acid ester compounds in the formation stage, so that their role in stabilizing the film structure can be further exerted during the later storage and cycle process. However, the combination of the above two will lead to an increase in the negative electrode interface impedance, limiting its application in environments that require lower impedance performance (such as low-temperature discharge).

[0009] Further research shows that when lithium salt additives with specific structures are added to the electrolyte containing the above-mentioned unsaturated carboxylic acid ester compounds with specific structures and cyclic sulfate compounds, they can modify the SEI film structure formed by the unsaturated carboxylic acid ester compounds at the negative electrode, thereby forming a flexible, thin and uniform SEI film on the surface of the negative electrode, which can reduce the membrane layer impedance and thus improve the low-temperature discharge capacity of the battery.

[0010] The objective of the present invention is achieved through the following technical solutions:

[0011] A lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound comprises a main lithium salt, a non-aqueous solvent and an additive, in particular, the additive comprises at least:

[0012] The first additive is an unsaturated carboxylic acid ester compound having a structure shown in the following formula (I):

[0013]

[0014] In formula (I), R1, R2, and R3 are independently selected from hydrogen or C1-C3 alkyl;

[0015] The second additive is selected from cyclic sulfate compounds having structures shown in the following formulas (II-A) and / or (II-B):

[0016]

[0017] In formula (II-A), G1, G2, G3, and G4 are independently selected from hydrogen, fluorine, methyl, or fluoromethyl;

[0018] In formula (II-B), G5, G6, G7, and G8 are independently selected from a direct bond, a methylene group, a fluoromethylene group, an alkyl-substituted methylene group, or a fluoromethyl-substituted methylene group, wherein M is selected from one of the following structures:

[0019]

[0020] Among them, G9, G 10 is independently selected from a direct bond or a methine group, m is selected from an integer of 0 to 6; n and o are independently selected from 1 or 2.

[0021] Preferably, in formula (I), R1, R2, and R3 are independently selected from hydrogen or methyl;

[0022] In formula (II-A), G1, G2, G3, and G4 are independently selected from hydrogen, fluorine, or methyl;

[0023] In formula (II-B), G5, G6, G7, and G8 are independently selected from a direct bond, a methylene group, or a trifluoromethyl-substituted methylene group, wherein M is selected from one of the following structures:

[0024]

[0025] Among them, G9, G 10 is independently selected from a direct bond or a methine group, m is selected from an integer of 0-4; n and o are independently selected from an integer of 1-4.

[0026] More preferably, the first additive is selected from at least one of the unsaturated carboxylic acid ester compounds represented by the following structural formula:

[0027]

[0028] The second additive is selected from at least one of the cyclic sulfate compounds represented by the following structure:

[0029]

[0030] In order to simultaneously meet the performance requirements of high temperature cycling and high temperature storage, the addition amounts of the first additive and the second additive account for a% and b% of the total mass of the electrolyte, respectively, and meet the following relationship:

[0031] 0.1≤a≤2, 0.1≤b≤2, and 0.2≤a+b≤3.5, 0.2≤a / b≤4

[0032] The first additive (unsaturated carboxylic acid ester compound) of the present invention contains unsaturated bonds at both ends, which can cross-link and polymerize on the electrode surface to form a stable polymer layer, thereby improving the high temperature stability of the battery, but it will increase the internal resistance of the battery and reduce the normal temperature and low temperature performance of the battery. By adding the second additive (cyclic sulfate compound), it can form an interface structure with the first additive at the negative electrode, thereby reducing the consumption of the first additive participating in film formation during the formation process, so that it can participate in the repair of the SEI film during the later cycle process, and improve the high temperature storage performance, high temperature cycle performance and normal temperature cycle performance of the battery.

[0033] However, the negative electrode interface impedance still needs to be improved by using only the first additive and the second additive. In order to further meet the performance requirements of low-temperature discharge of the battery, a third additive needs to be added, and the third additive is selected from at least one of the lithium salt additives represented by the following formula (III-1), (III-2) or (III-3):

[0034]

[0035] Further adding lithium salt additives on the basis of the first additive and the second additive can generate components with high ionic conductivity such as fluorophosphate on the electrode surface, improve the ion conductivity of the interface film layer, inhibit the decomposition of lithium hexafluorophosphate, and thus effectively reduce the content of low-conductivity LiF in the interface, reduce the internal resistance of the battery, and improve the battery cycle stability and low-temperature discharge performance.

[0036] The amount of the third additive added is c% of the total mass of the electrolyte and meets the following relationship:

[0037] 0.1≤c≤1.5, and 1≤(a+b) / c≤4.8.

[0038] Preferably, the addition amounts of the first additive, the second additive and the third additive meet the following relationship:

[0039] 0.3≤a≤1, 0.2≤b≤0.8, 0.3≤c≤0.9; and,

[0040] 0.5≤a+b≤1.4, 0.5≤a / b≤2.5, 1.2≤(a+b) / c≤2.5.

[0041] If the ratio of the first additive to the second additive (a / b) is too large (e.g. >4), and the first additive content (a) is too high (e.g. >2), the first additive content will drop significantly after the formation step, and the low-temperature discharge performance will deteriorate; in the long-cycle evaluation, the capacity will also decay rapidly in the late high-temperature cycle. It is speculated that the reason may be that too much first additive preferentially undergoes a reduction reaction at the negative electrode, forming a thicker SEI film layer, which consumes a large amount of active lithium and increases R SEI , which deteriorates the low-temperature performance and makes its remaining content insufficient for repairing the ruptured membrane layer in the later stage of high-temperature cycling.

[0042] If the ratio of the first additive to the second additive (a / b) is too small (such as <0.2), and the content of the first additive (a) is too low (such as <0.1), the excess of the second additive will lead to the deterioration of the low-temperature discharge performance and significantly increase the impedance, and the high-temperature cycle performance is not as good as using the first additive alone. It is speculated that the reason may be that the second additive cannot provide a more stable SEI film structure, but its lower reduction potential still causes it to produce a large amount of reduction products at the negative electrode, resulting in an increase in the SEI film thickness and an increase in impedance.

[0043] If the sum of the first additive and the second additive (a+b) is too large (e.g. >3.5), and the ratio to the third additive ((a+b) / c) is too large (e.g. >4.8), although the addition of the second additive in an appropriate proportion reduces the consumption of the first additive in the formation stage and improves the stability of high-temperature cycles, it is accompanied by further deterioration of low-temperature discharge performance, such as severe lithium deposition during low-temperature charging. The reason may be that the proportion of organic components in the SEI film structure formed is too high, which is not conducive to the rapid diffusion of lithium ions in the interface layer.

[0044] If the sum of the first additive and the second additive (a+b) is too small (eg <0.2), and the ratio thereof to the third additive ((a+b) / c) is too small (eg <1), although the impedance is not degraded, it has no positive effect on the high temperature performance.

[0045] When and only when the first additive with a specific functional group is combined with the second additive in a certain range of proportions, and the ratio of the sum of the contents of the two to the third additive is also within an appropriate range, the consumption of the first additive in the formation process can be effectively controlled. On the one hand, the SEI film formed by the three additives can take into account both the toughness of the organic film layer and the rigidity of the inorganic film layer, forming an effective ion-conducting structure, providing the stability of high-temperature cycles and the low-impedance characteristics required for low-temperature discharge; on the other hand, the appropriate consumption of the first additive in the formation stage can also provide effective assistance to the SEI film in the subsequent cycles during damage and repair, further improving the cycle performance and high-temperature storage performance.

[0046] In the lithium-ion battery electrolyte of the present invention, the main lithium salt can be a lithium salt commonly used in electrolytes. Preferably, the main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide, and the concentration in the electrolyte is 8-20wt%;

[0047] More preferably, the main lithium salt is selected from lithium hexafluorophosphate and / or lithium bis(fluorosulfonyl)imide, and the mass concentration in the electrolyte is 10-15 wt%.

[0048] In the lithium-ion battery electrolyte of the present invention, the non-aqueous solvent can be any organic solvent commonly used in electrolytes. Preferably, the non-aqueous solvent is selected from at least one of C3-C6 carbonate or fluorinated carbonate compounds, C3-C8 carboxylic acid ester or fluorinated carboxylic acid ester compounds, sulfone compounds or ether compounds.

[0049] More preferably, the C3-C6 carbonate or fluorocarbonate compound is at least one selected from ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, fluoroethylene carbonate or difluoroethylene carbonate;

[0050] The C3-C8 carboxylic acid ester or fluorocarboxylic acid ester compound is selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate, propyl propionate or ethyl fluoroacetate, ethyl 2,2-difluoroacetate, ethyl 2,2,2-trifluoroacetate, ethyl 2,2-difluoropropionate and propyl 2,2-difluoropropionate;

[0051] The sulfone compound is selected from at least one of sulfolane, dimethyl sulfoxide, dimethyl sulfone or diethyl sulfone;

[0052] The ether compound is selected from at least one of diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether or 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0053] Further, the non-aqueous solvent is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, propyl propionate, ethyl 2,2-difluoroacetate, ethyl 2,2,2-trifluoroacetate, ethyl 2,2-difluoropropionate, and propyl 2,2-difluoropropionate.

[0054] In the actual electrolyte formulation application process, organic solvents are all complex multi-component systems, among which cyclic carbonates have high dielectric constants and can better dissolve lithium salts to provide high conductivity; linear carbonates and carboxylates can effectively adjust the viscosity and liquid range of the electrolyte, and various types of solvents are matched to achieve a more suitable organic solvent system with various comprehensive properties. Therefore, the non-aqueous solvent of the present invention is preferably a composite solvent formed by cyclic carbonates (ethylene carbonate and / or propylene carbonate), linear carbonates (at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate) or linear carboxylates (at least one of methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, and propyl propionate) in a certain ratio.

[0055] In the actual electrolyte formula application process, the electrolyte formula is a complex multi-component system to obtain a lithium secondary battery with balanced and excellent comprehensive performance. Therefore, the electrolyte of the present invention also includes a basic additive, which is selected from vinylene carbonate, 1,3-propane sultone, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluoro oxalate borate, lithium bisoxalate difluorophosphate, lithium oxalate tetrafluorophosphate, tris (trimethylsilyl) phosphate, tris (trimethylsilyl) borate, succinonitrile, glutaronitrile, adiponitrile, trans-butene dinitrile, trans-hexene dinitrile, 1,2-bis (cyanoethoxy) ethane, 1,3,6-hexane tricarbonitrile, 1,2,3-tris (cyanoethoxy) propane At least one, the addition amount of any basic additive accounts for 0.1 to 5.0wt% of the total mass of the electrolyte. As preferably, the addition amount of any basic additive accounts for 0.2 to 3.0wt% of the total mass of the electrolyte.

[0056] In a specific embodiment, the basic additive uses 0.1-2.0wt% of vinylene carbonate and 0.1-2.0wt% of lithium difluorooxalate borate. Through the combination of vinylene carbonate, lithium difluorooxalate borate and the first additive, the second additive and the third additive, the cycle stability of the battery is further improved on the basis of improving the normal temperature and high temperature cycle performance, high temperature storage performance and low temperature discharge performance of the lithium-ion battery.

[0057] The present invention also provides a lithium ion secondary battery, which comprises a positive electrode, a negative electrode, a separator and any one of the above-mentioned lithium ion battery electrolytes containing unsaturated carboxylic acid ester compounds.

[0058] The active material of the positive electrode is selected from at least one of nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium cobalt oxide material, layered nickel-manganese oxide material, lithium-rich manganese-based material, lithium iron phosphate material or lithium iron manganese phosphate material.

[0059] The active material of the negative electrode is selected from at least one of graphite, silicon carbon, silicon dioxide, silicon, tin, metallic lithium or a composite material thereof.

[0060] Compared with the prior art, the present invention has the following technical effects:

[0061] 1. The present invention uses unsaturated carboxylic acid ester compounds and cyclic sulfate compounds in combination, which can fully utilize the high SEI film-forming stability of the unsaturated carboxylic acid ester compounds. When the contents of the two are within a fixed ratio range, it can ensure that they are not completely consumed in the battery formation stage, thereby improving high-temperature cycle and storage stability;

[0062] 2. The present invention uses a lithium salt additive with a specific structure in combination with the above two additives, and at the same time regulates the distribution of the three additive contents. Through the synergistic effect of the three additives, they can form a film on the electrode surface to generate an organic-inorganic composite interface layer, thereby further improving the low-temperature discharge performance of the battery. DETAILED DESCRIPTION

[0063] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.

[0064] 1. Preparation of Nickel-Cobalt-Manganese Ternary Battery Electrolyte

[0065] Preparation of basic electrolyte: In a glove box filled with argon (water content <5ppm, oxygen content <10ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are uniformly mixed in a mass ratio of EC:EMC:DEC=3:5:2 to form an organic solvent. Based on the total mass of the electrolyte, lithium hexafluorophosphate is added in a mass percentage of 14% and used as a basic electrolyte.

[0066] According to the data in Table 1 below, vinylene carbonate (VC), lithium difluorooxalatoborate (LiODFB), an unsaturated carboxylic acid ester compound (first additive), a cyclic sulfate ester compound (second additive) and a lithium salt additive (third additive) are quantitatively added to the basic electrolyte and mixed evenly to form an electrolyte:

[0067] Table 1: Electrolyte formula of examples and comparative examples

[0068]

[0069]

[0070] 2. Nickel-cobalt-manganese ternary battery production and performance testing

[0071] The lithium-ion battery electrolytes of the above examples and comparative examples are respectively made into soft-pack lithium-ion power batteries with a capacity of 1000 mAh, wherein the lithium-ion power batteries include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material of the battery is LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), the negative electrode active material is artificial graphite (AG).

[0072] The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a core, which is sealed with an aluminum-plastic film and then baked so that the moisture content of the electrode meets the requirements. After baking, the battery cell is injected with electrolyte, and the finished soft-pack battery cell is obtained through the steps of standing, forming, capacity separation and aging.

[0073] The above lithium-ion batteries are tested for various performances, including:

[0074] (1) Cyclic performance test

[0075] At a specified temperature, charge at a constant current of 1C to the charge cut-off voltage (4.4V), then charge at a constant voltage until the current drops to 0.1C, then discharge at a constant current of 1C to the cut-off voltage (2.8V), and repeat this cycle for a specific number of weeks. Record the discharge capacity of the first week and the discharge capacity of the last week, and calculate the capacity retention rate of the battery cycle as follows:

[0076] Capacity retention rate = discharge capacity in the last week / discharge capacity in the first week×100%.

[0077] (2) High temperature storage performance test

[0078] At room temperature, charge at a constant current of 1C to the charge cut-off voltage, and charge at a constant voltage until the current drops to 0.1C, and then place in a 60℃ constant temperature oven for 56 days. When the battery after storage cools to room temperature, record the initial volume and the volume after storage:

[0079] Volume expansion ratio = (volume after storage - volume before storage) / volume before storage × 100%.

[0080] (3) Low temperature discharge capacity

[0081] At room temperature, the battery was charged at a constant current of 0.5C to the charge cut-off voltage, then charged at a constant voltage until the current dropped to 0.1C, and then discharged at a constant current of 0.5C to the discharge cut-off voltage at low temperature, and the discharge capacity at low temperature was recorded.

[0082] Low temperature discharge capacity retention rate = low temperature discharge capacity / room temperature discharge capacity * 100%.

[0083] (4) Additive consumption

[0084] The battery is tested according to a specified procedure, including but not limited to formation, capacity division, cycle, discharge, etc., and a certain mass of inert internal standard (methyl acetate is used in this embodiment) is used as a benchmark. The electrolyte samples obtained before and after the formation are tested by gas chromatography for changes in the content of specified additives, and the mass of the additives before and after the formation is recorded:

[0085] Additive formation consumption = (mass of additive before formation - mass of additive after formation) / mass of additive before formation × 100%.

[0086] The specific test results are shown in Table 2 and Table 3 below:

[0087] Table 2 NCM622||AG-4.4V electrochemical test results

[0088]

[0089]

[0090] Table 3 Results of the chemical consumption test of the first additive in NCM622||AG

[0091] Example / Comparative Example Consumption of the first additive / % Comparative Example 2 92.33 Comparative Example 3 87.66 Example 1 57.12 Example 2 46.54 Embodiment 22 35.51 Embodiment 25 37.59 Embodiment 27 46.73

[0092] According to Table 2 above, by comparing Comparative Example 1 with Comparative Examples 2 and 3, it can be seen that the use of the first additive alone can improve the room temperature and high temperature cycle capacity retention rate and high temperature storage stability as its content increases, but it also significantly deteriorates the low temperature discharge performance; by comparing Comparative Example 1 with Comparative Examples 4, 5, 6, and 7, it can be seen that the use of the second additive alone does not improve the high temperature cycle performance as much as the use of the first additive alone, and its lower reduction potential still causes it to produce a large amount of reduction products at the negative electrode, resulting in an increase in the thickness of the SEI film, increasing the negative electrode impedance and causing low temperature performance degradation; by comparing Comparative Example 1 with Comparative Examples 8 and 9, it can be seen that the use of the third additive alone can improve the room temperature cycle and low temperature discharge performance, but has no significant positive effect on its high temperature cycle and high temperature storage performance. By comparing Comparative Example 1 with Examples 1-6, it can be seen that the combination of the first additive and the second additive can improve the high temperature cycle performance after 300 weeks, which is related to the second additive inhibiting the formation consumption of the first additive, but the low temperature discharge performance is still poor.

[0093] By comparing Examples 7-20 and Comparative Examples 10-17, it can be seen that only when the contents of the first additive, the second additive and the third additive satisfy 0.1≤a≤2, 0.1≤b≤2, 0.1≤c≤1.5, and the three satisfy the relationship 0.2≤a+b≤3.5, 0.2≤a / b≤4, 1≤(a+b) / c≤4.8, can a stable interface be achieved to reduce the internal resistance of the battery interface while improving the interface stability, thereby significantly improving the battery's room temperature, high temperature cycle performance, high temperature storage and low temperature discharge performance.

[0094] Comparing Examples 7-20 and 21-29, it can be seen that by regulating the contents of the three additives, when the contents of the three respectively satisfy 0.3≤a≤1, 0.2≤b≤0.8, 0.3≤c≤0.9, and the relationship between them satisfies 0.5≤a+b≤1.4, 0.5≤a / b≤2.5, 1.2≤(a+b) / c≤2.5, the normal temperature and high temperature cycle performance, high temperature storage and low temperature discharge performance of the battery can be further improved. The compound corresponding to the first additive, the compound corresponding to the second additive and the compound corresponding to the third additive all have the functions of the additives represented and can be used interchangeably.

[0095] By comparing Examples 28, 29, and 30 with Examples 31, 32, and 33, it can be seen that the adjustment of the addition amount of the basic additives VC and LiODFB slightly improves the battery cycle performance and slightly deteriorates the battery low-temperature discharge performance. The possible reason is speculated to be that VC and LiODFB, as film-forming additives, can enhance the strength of the electrode interface, alleviate the loss of active lithium caused by interface damage repair during charge and discharge, and improve the cycle performance. However, when the addition amount is increased, the increase in film thickness may lead to a decrease in the interfacial lithium ion transport kinetics, thereby reducing the battery low-temperature discharge performance.

[0096] According to Table 3 above, by comparing Comparative Examples 2 and 3 with Examples 1 and 2, it can be seen that with the addition of the second additive, the consumption of the first additive after formation gradually decreases as the concentration of the second additive increases, but because there is no addition of the third additive, the low temperature performance is still poor; comparing Examples 22, 25, and 27, the increase of the second additive can suppress the consumption of the first additive in a certain range, and when all three additives are added and the ratio is in line with the optimized range, the battery has the best normal temperature cycle, high temperature cycle, high temperature storage and low temperature discharge performance.

[0097] 3. Preparation of lithium iron manganese phosphate battery electrolyte

[0098] Preparation of basic electrolyte: In a glove box filled with argon (water content <5ppm, oxygen content <10ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are uniformly mixed in a mass ratio of EC:EMC:DEC=3:5:2 to form an organic solvent. Based on the total mass of the electrolyte, lithium hexafluorophosphate is added in a mass percentage of 14% and used as a basic electrolyte.

[0099] According to the data in Table 4 below, vinylene carbonate (VC), 1,3-propane sultone (PS), an unsaturated carboxylic acid ester compound (first additive), a cyclic sulfate compound (second additive) and a lithium salt additive (third additive) are quantitatively added to the basic electrolyte and mixed evenly to form an electrolyte:

[0100] Table 4: Electrolyte formula of examples and comparative examples

[0101]

[0102] 4. Manganese iron phosphate lithium battery production and performance testing

[0103] The lithium-ion battery electrolytes of the above examples and comparative examples are respectively made into soft-pack lithium-ion power batteries with a capacity of 1000 mAh, wherein the lithium-ion power batteries include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material of the battery is LiMn 0.7 Fe 0.3 PO4 (LMFP), the negative electrode active material is artificial graphite (AG);

[0104] The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a core, which is sealed with an aluminum-plastic film and then baked so that the moisture content of the electrode meets the requirements. After baking, the battery cell is injected with electrolyte, and the finished soft-pack battery cell is obtained through the steps of standing, forming, capacity separation and aging.

[0105] The above lithium-ion batteries are tested for various performances, including:

[0106] (1) Cyclic performance test

[0107] At a specified temperature, charge at a constant current of 1C to the charge cut-off voltage (4.25V), then charge at a constant voltage until the current drops to 0.1C, then discharge at a constant current of 1C to the cut-off voltage (2.8V), and repeat this cycle for a specific number of weeks. Record the discharge capacity of the first week and the discharge capacity of the last week, and calculate the capacity retention rate of the battery cycle as follows:

[0108] Capacity retention rate = discharge capacity in the last week / discharge capacity in the first week×100%.

[0109] (2) High temperature storage performance test

[0110] At room temperature, charge at a constant current of 1C to the charge cut-off voltage, and charge at a constant voltage until the current drops to 0.1C, and then place in a 60℃ constant temperature oven for 56 days. When the battery after storage cools to room temperature, record the initial volume and the volume after storage:

[0111] Volume expansion ratio = (volume after storage - volume before storage) / volume before storage × 100%.

[0112] (3) Low temperature discharge capacity

[0113] At room temperature, the battery was charged at a constant current of 0.5C to the charge cut-off voltage, then charged at a constant voltage until the current dropped to 0.1C, and then discharged at a constant current of 0.5C to the discharge cut-off voltage at low temperature, and the discharge capacity at low temperature was recorded.

[0114] Low temperature discharge capacity retention rate = low temperature discharge capacity / room temperature discharge capacity * 100%.

[0115] (4) Additive consumption

[0116] The battery is tested according to a specified procedure, including but not limited to formation, capacity division, cycle, discharge, etc., and a certain mass of inert internal standard (methyl acetate is used in this embodiment) is used as a benchmark. The electrolyte samples obtained before and after the formation are tested by gas chromatography for changes in the content of specified additives, and the mass of the additives before and after the formation is recorded:

[0117] Additive formation consumption = (mass of additive before formation - mass of additive after formation) / mass of additive before formation × 100%.

[0118] The specific test results are shown in Table 5 and Table 6 below:

[0119] Table 5 LMFP||AG-4.25V electrochemical test results

[0120]

[0121] Table 6 Chemical formation consumption test results of the first additive in LMFP||AG

[0122] Example / Comparative Example Consumption of the first additive / % Embodiment 37 46.68 Embodiment 38 39.24 Embodiment 39 36.82

[0123] According to Table 5 above, by comparing Comparative Example 18 with Comparative Examples 19, 20, and 21, it can be seen that the use of the first additive alone can improve the normal temperature and high temperature cycle capacity retention rate and high temperature storage stability, and the use of the second additive alone does not improve the high temperature cycle performance as much as the use of the first additive alone, and the use of the third additive alone can improve the normal temperature cycle and low temperature discharge performance, but has no significant positive effect on its high temperature cycle and high temperature storage performance. By comparing Comparative Example 18 with Examples 34-39, it can be seen that the use of the first additive and the second additive in combination can improve the high temperature cycle performance after 300 weeks, which is related to the second additive suppressing the formation consumption of the first additive, but the low temperature discharge performance is still poor.

[0124] Comparing Examples 37, 38, 39 with Comparative Examples 22 and 23, it can be seen that only when the contents of the first additive, the second additive and the third additive satisfy 0.1≤a≤2, 0.1≤b≤2, 0.1≤c≤1.5, and the three satisfy the relationship 0.2≤a+b≤3.5, 0.2≤a / b≤4, 1≤(a+b) / c≤4.8, can a stable interface be achieved to reduce the internal resistance of the battery interface while improving the interface stability, thereby significantly improving the normal temperature and high temperature cycle performance, high temperature storage and low temperature discharge performance of the battery. Furthermore, when the contents of the three respectively satisfy 0.3≤a≤1, 0.2≤b≤0.8, 0.3≤c≤0.9, and when they mutually satisfy the relationship 0.5≤a+b≤1.4, 0.5≤a / b≤2.5, 1.2≤(a+b) / c≤2.5, the battery performance can be further improved.

[0125] By comparing Examples 34-39 with Examples 40 and 41, it can be seen that the adjustment of the addition amount of the basic additives VC and PS slightly improves the battery cycle performance and slightly deteriorates the battery low-temperature discharge performance. The possible reason is speculated to be that VC and PS as film-forming additives can enhance the strength of the electrode interface, alleviate the loss of active lithium caused by interface damage repair during charging and discharging, and improve the cycle performance. However, when the addition amount is increased, the increase in VC film thickness may lead to a decrease in the interfacial lithium ion transfer kinetics and reduce the low-temperature discharge performance of the battery.

[0126] According to Table 6 above, by comparing Examples 37, 38, and 39, it can be seen that the increase of the second additive can suppress the formation consumption of the first additive within a certain range, and when all three additives are added and the proportions are in line with the optimized range, the battery has optimal normal temperature cycle, high temperature cycle, high temperature storage, and low temperature discharge performance.

Claims

1. A lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound, comprising a main lithium salt, a non-aqueous solvent and an additive, characterized in that: The additives include at least: The first additive is an unsaturated carboxylic acid ester compound having a structure represented by the following formula (I): In formula (I), R1, R2, and R3 are independently selected from hydrogen or C1-C3 alkyl; The second additive is selected from cyclic sulfate compounds having structures shown in the following formulas (II-A) and / or (II-B): In formula (II-A), G1, G2, G3, and G4 are independently selected from hydrogen, fluorine, methyl, or fluoromethyl; In formula (II-B), G5, G6, G7, and G8 are independently selected from a direct bond, a methylene group, a fluoromethylene group, an alkyl-substituted methylene group, or a fluoromethyl-substituted methylene group, wherein M is selected from one of the following structures: Among them, G9, G 10 is independently selected from a direct bond or a methine group, m is selected from an integer of 0-6; n and o are independently selected from an integer of 1-4.

2. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 1, characterized in that: In formula (I), R1, R2, and R3 are independently selected from hydrogen or methyl; In formula (II-A), G1, G2, G3, and G4 are independently selected from hydrogen, fluorine, or methyl; In formula (II-B), G5, G6, G7, and G8 are independently selected from a direct bond, a methylene group, or a trifluoromethyl-substituted methylene group, wherein M is selected from one of the following structures: Among them, G9, G 10 is independently selected from a direct bond or a methine group, m is selected from an integer of 0 to 4; n and o are independently selected from 1 or 2.

3. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 2, characterized in that: The first additive is selected from at least one of the unsaturated carboxylic acid ester compounds represented by the following structural formula:

4. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 2, characterized in that: The second additive is selected from at least one of the cyclic sulfate compounds represented by the following structure:

5. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 1, characterized in that: The addition amounts of the first additive and the second additive account for a% and b% of the total mass of the electrolyte respectively, and meet the following relationship: 0.1≤a≤2, 0.1≤b≤2 and 0.2≤a+b≤3.5, 0.2≤a / b≤4.

6. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 5, characterized in that: The addition amounts of the first additive and the second additive meet the following relationship: 0.3≤a≤1, 0.2≤b≤0.8 and 0.5≤a+b≤1.4, 0.5≤a / b≤2.

5.

7. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to any one of claims 1 to 6, characterized in that: The electrolyte further includes a third additive, and the third additive is selected from at least one of the lithium salt additives having the structures shown in the following formula (III-1), (III-2) or (III-3):

8. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 7, characterized in that: The amount of the third additive added accounts for c% of the total mass of the electrolyte and meets the following relationship: 0.1≤c≤1.5 and 1≤(a+b) / c≤4.

8.

9. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 8, characterized in that: The amount of the third additive added conforms to the following relationship: 0.3≤c≤0.9 and 1.2≤(a+b) / c≤2.

5.

10. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 1, characterized in that: The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide, and its usage accounts for 8-20wt% of the total mass of the electrolyte.

11. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 1, characterized in that: The non-aqueous solvent is selected from at least one of C3-C6 carbonate or fluorinated carbonate compounds, C3-C8 carboxylic acid ester or fluorinated carboxylic acid ester compounds, sulfone compounds or ether compounds.

12. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to claim 11, characterized in that: The non-aqueous solvent is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, propyl propionate, ethyl 2,2-difluoroacetate, ethyl 2,2,2-trifluoroacetate, ethyl 2,2-difluoropropionate, and propyl 2,2-difluoropropionate.

13. The lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound according to any one of claims 1 to 12, characterized in that: The electrolyte further includes a basic additive, which is selected from at least one of vinylene carbonate, 1,3-propane sultone, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(oxalatodifluorophosphate), lithium oxalatotetrafluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, succinonitrile, glutaronitrile, adiponitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,2-bis(cyanoethoxy)ethane, 1,3,6-hexanetricarbonitrile or 1,2,3-tris(cyanoethoxy)propane, and the addition amount of any basic additive accounts for 0.1 to 5.0 wt% of the total mass of the electrolyte.

14. A lithium ion secondary battery comprising a positive electrode, a negative electrode and a separator, characterized in that: The lithium ion secondary battery further comprises a lithium ion battery electrolyte containing an unsaturated carboxylic acid ester compound as claimed in any one of claims 1 to 13.

Citation Information

Patent Citations

  • Nonaqueous electrolyte for lithium battery and lithium battery using same

    CN101981749A

  • Nonaqueous electrolyte secondary battery

    JP2009152133A